Organotypic brain slice cultures as a model to study angiogenesis of brain vessels - Hutter-Schmid, Bianca; Kniewallner, Kathrin M.; Humpel, Christian (Frontiers in Cell and Developmental Biology, 2015)
Brain vessels are the most important structures in the brain to deliver energy and substrates to neurons. Brain vessels are composed of a complex interaction between endothelial cells, pericytes and astrocytes, controlling the entry of substrates into the brain. Damage of brain vessels and vascular impairment are general pathologies observed in different neurodegenerative disorders including e.g. Alzheimer´s disease. In order to study remodeling of brain vessels, simple 3-dimensional in vitro systems need to be developed. Organotypic brain slices of mice provide a potent tool to explore angiogenic effects of brain vessels in a complex 3-dimensional structure. Here we show that organotypic brain slices can be cultured from 110 µm thick sections of postnatal and adult mice brains. The vessels are immunohistochemically stained for laminin and collagen IV. Co-stainings are an appropriate method to visualize interaction of brain endothelial cells with pericytes and astrocytes in these vessels. Different exogenous stimuli such as fibroblast growth factor-2 or vascular endothelial growth factor induce angiogenesis or re-growth, respectively. Hyperthermia or acidosis reduces the vessel density in organotypic slices. In conclusion, organotypic brain slices exhibit a strong vascular network which can be used to study remodeling and angiogenesis of brain vessels in a 3-dimensional in vitro system.